Academic Hardiness Level of Guidance and Counseling Study Program Students Post Covid 19 Pandemic - Setyowati, Aprilia; Fauziah, Mufied; Farozin, Muh; Astuti, Budi; Rifqoh, Fany (Universitas Mathla'ul Anwar Banten, 2024)
The purpose of this study is to inform the condition of Academic hardiness of Ahmad Dahlan University Guidance and Counseling Study Program students after the Covid-19 pandemic. Academic hardiness is a personality that is resilient in various obstacles, especially stress. Academic hardiness is a variable that must be possessed by students in order to achieve achievement while studying. The research population is 152 active students for the 2019-2021 academic year. This type of research uses quantitative descriptive. Data were obtained using an academic hardiness scale developed based on Kobasa's theory and Dweck's theory related to academic motivation. The scale developed refers to 3 aspects of academic hardiness namely commitment, challenge, and control. The developed scale was analyzed using the Rach Model. The results of the analysis stated that the 17 items developed contained several notes and needed to be revised. The results showed that the level of student academic hardiness of 89.5% was in the high category, 10.5% was in the medium category, and 0% was in the low category. Based on the research results, it is recommended that further researchers develop a counseling model to develop students' Academic hardiness, especially those who are still in the moderate category.